Photocatalytic activity of ZNO with different morphologies synthesized by a sonochemical method - Anukorn Phuruangrat (2018)
© 2016, Pleiades Publishing, Ltd. Different morphologies of ZnO structures were successfully synthesized in precursor solutions with the pH of 8, 9, 10, 11, and 12 by a sonochemical method at room temperature. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR) and Raman spectroscopy. The photocatalytic activities of ZnO samples with different morphologies were evaluated via the degradation of methylene blue (C16H18ClN3S). In this research, the flower-like ZnO sample of densely assembled nanoplates exhibited the highest photodegradation of 64% under UV light irradiation within 300 min.